Integrating constructivist learning environments (CLEs) in designing a multimedia learning application for cyber-bullying intervention / Nadia Abdul Wahab ...[et al.] - Abdul Wahab, Nadia; Osman, Aznoora; Ibrahim, Norfiza; Md Ilyas, Siti Sarah (UiTM Cawangan Perlis, 2021)
Constructivism is a learning theory that emphasizes learners’ intervention through self-guided exploration, reflection, and evaluation. This study discusses on the integration of the Constructivist Learning Environments (CLEs) in designing a multimedia learning application for cyber-bullying intervention among adolescents. The application has been evaluated using Alpha Testing and Beta Testing technique to ensure its quality. From this evaluation, the researcher was also able to identify weaknesses or problems associated with the usage of the application, from the viewpoint of the content and multimedia expert and also the target user group which are the adolescents. By integrating CLEs, it is expected that knowledge and awareness is constructed by the learners as they reconcile new information with past experiences, analyze various source materials, and work collaboratively with others. As CLEs stimulates active learning, it is hoped that leaners will develop advanced skills such as critical thinking, analysis, evaluation, and creation. As CLEs promotes diverse viewpoints, it encourages students to reflect, evaluate their work, and identify intermediary skills to acquire based on their needs. It is also expected that the development of the multimedia app in this study will contributed to an increase in the number of computer-based applications intended to expose adolescents to the issue of cyber-bullying, which is still under-developed, particularly in the context of adolescents in Malaysia.